Time Management and Patience Internalisation Among Islamic Education Students During Community Service and Hybrid Learning - Rifka Nadiana; Fitriah M. Suud (Universitas Nurul Jadid, 2026)
This research is motivated by students' simultaneous demands for hybrid learning and Community Service Program (KKN) activities. These conditions require students to apply time management and patience to balance both. This study aims to analyse time management and the internalisation of patience values among Islamic Education (PAI) students in the context of community service (KKN) and hybrid lectures, from an Islamic education perspective. This research uses a qualitative, phenomenological approach. The research participants were seven PAI students selected through purposive sampling. Data were obtained through in-depth interviews and analysed using thematic analysis, following the methods of Virginia Braun and Victoria Clarke. The research results show that students interpret time management as the ability to set priorities, allocate time, and maintain a balance between two activities. In addition, the attitude of patience is internalised through the ability to control emotions, accept results that do not meet expectations, and endure a busy schedule. Factors that influence patience include internal factors such as faith, physical condition, and emotional maturity, as well as external factors such as the social environment and academic workload. The strategies employed by students include applying a priority scale, planning activities, self-reflection, emotional control, and a religious approach. This research shows that time management skills and the internalisation of values of patience are important factors in shaping students' ability to perform dual roles effectively. Therefore, higher education institutions need to provide academic support and strengthen spiritual values to help students meet the demands of hybrid learning and community service activities.